Intravenous leiomyomatosis - Narayanaswamy Mariyappa; Uday Kumar Manikyam; Dinesh Krishnamurthy; K Preeti; Yamini Agarwal; U Prakar (Nigerian Journal of Surgery, 2012)
Leiomyomas are benign tumors arising from smooth muscle of the uterus. Intravenous leiomyomatosis is characterized by intraluminal growth of benign smooth muscle into either venous or lymphatic vessels outside the limits of myoma. It commonly extends into the pelvic veins and manifests as worm-like protrusions of tumor emanating from veins at the parametrial margins of hysterectomy specimen. The tumor can cause life-threatening symptoms if it involves inferior vena cava or right atrium. We report a case of intravenous leiomyomatosis of the uterus managed at our institution.